Pneumocystis carinii pneumonia: a light microscopical and ultrastructural study. Issue 10 (October 1981) - Hasleton, P S; Curry, A; Rankin, E M
Abstract : A case of Pneumocystis carinii pneumonia developing a patient with treated diffuse lymphocytic lymphoma is described. The electron microscopic features and life cycle of the organism are illustrated. The patient died twenty-four hours after the biopsy had been taken. Septrin appeared to have affected the trophozoite stage. Pneumocystis carinii appears to induce interstitial pulmonary oedema and fibrosis. A discussion of the role of electron microscopy in early diagnosis of the disease is presented.